INTERAKSI ETIKA DAN MOTIVASI TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT APARAT INSPEKTORAT - Theophilia Fina F Leiwakabessy; Revy W Silooy (RISTANSI: Riset Akuntansi, 2021)
This study aims to examine ethics as a moderator of the relationship between competence and independence of auditors with the audit quality of the inspectorate apparatus. The population of this study were employees of the Inspectorate of Maluku Province and Ambon City. Sampling used judgment sampling method with a total sample of 73 respondents. The data collection technique used is a survey technique using a questionnaire. Data analysis used moderated regression analysis (MRA). The results showed that competence had no effect on audit quality, auditor independence had no effect on audit quality. Furthermore, auditor ethics can moderate the relationship between competence and independence of auditors with audit quality, while motivation cannot moderate the relationship between competence and independence of auditors with audit quality.